Primary Malignant Melanoma of Maxilla: Report of a Case with Discussion - G. Shirisha Rani; T. Vinay Kumar; Balaram Kolasani; Md Rezwana Begum; Anu Priya Srinivasan (Case Reports in Dentistry)
Primary oral malignant melanoma, very rare neoplasm of melanocytic origin, usually presents as a bluish black to tan-brown colored lesion Which is accounting for 0.2 to 8% of all melanomas, 1.6% of all head and neck malignancies, and 0.5% of all oral neoplasia. In general, the prognosis of oral melanoma is poor and worse than that of cutaneous melanoma. Here a case of oral malignant melanoma is presented, which was undetected during the first visit to a dental clinic. When a simple oral surgical treatment was carried out in that region, it resulted in the appearance of a massive pigmented lesion which was histopathologically diagnosed as malignant melanoma. This paper is presented to reemphasize the fact that any pigmented lesion in the oral cavity should be viewed with suspicion and proper investigation (biopsy) should be carried out to rule out any untoward experiences later.